Development and Validation of Stability-indicating HPLC Method for Estimation of Azilsartan in Pharmaceutical and Solid Lipid Nanoparticles - Bhasagi, Neha Sanjay; Kurangi, Bhaskar Kallappa; Mane, Vishal Arvind; Patil, Swapnil Pandurang; Soudagar, Moazzim Mainoddin; Chimgave, Supriya Suresh (Indian Journal of Pharmaceutical Education and Research, 2024)
Introduction: Azilsartan has been scientifically proven to be effective in treating hypertension. According to International Conference on Harmonization, the HPLC method was developed and validated to estimate the azilsartan in formulated solid lipid nanoparticles and marketed pharmaceutical formulations. Objectives: Develop and validate an HPLC method for analysing azilsartan in drugs and various formulations that demonstrated stability by ICH (International Conference on Harmonization) standards. Materials and Methods: The mobile phase uses methanol: phosphate buffer (0.1% orthophosphoric acid, pH 3.2) (70:30), having the chromatographic separator is an HPLC column C18 (4.6 mm X 250 mm) with a wavelength of 249 nm and a flow rate of 1 mL/min. Results: The developed method showed a correlation coefficient value is 0.999 and to be linear throughout a concentration range of 2-10 μg/mL. The proposed method was precise (percent RSD 2.0%), accurate (percent recovery 99-101%), and reliable. The detection and quantification limits for azilsartan were determined to be 0.01 μg/mL and 0.04 μg/mL, respectively. According to ICH criteria, the developed method was validated and a stress degradation study was conducted. The developed method was used to estimate azilsartan in solid lipid nanoparticles to determine the applicability of the developed method. Conclusion: A quick, accurate, simple and economical HPLC method was successfully developed and validated for the estimation of azilsartan in solid lipid nanoparticles and marketed formulation.
Keywords: Azilsartan; Solid Lipid Nanoparticle; HPLC; Method Development; Degradation Study